2022
DOI: 10.1021/acsami.2c13150
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling Parasitic Reactions at the Positive Electrode Interfaces in Argyrodite-Based Systems

Abstract: Li-ion batteries are the key stones of electric vehicles, but with the emergence of solid-state Li batteries for improving autonomy and fast charging, the need for mastering the solid electrolyte (SE)/electrode material interfaces is crucial. All-solid-state-batteries (ASSBs) suffer from long-term capacity fading with enhanced decomposition reactions. So far, these reactions have not been extensively studied in Li6PS5Cl-based systems because of the complexity of overlapping degradation mechanisms. Herein, thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…A similar observation was made with Raman measurements on the LiCoO 2 and Li 6 PS 5 Cl solid–solid interface, 9 highlighting the oxidative stability of the electrolyte breakdowns when in contact with partially de-lithiated positive electrode materials. Though the negative effects of carbon additives on degradation have been frequently reported, 29,30 from this initial study no correlation of the degradation products with carbon position was observed. Mapping studies, using a variety of carbons will be probed, as well as in situ mapping investigations to further understand the origin and location of composite electrode degradation.…”
mentioning
confidence: 52%
“…A similar observation was made with Raman measurements on the LiCoO 2 and Li 6 PS 5 Cl solid–solid interface, 9 highlighting the oxidative stability of the electrolyte breakdowns when in contact with partially de-lithiated positive electrode materials. Though the negative effects of carbon additives on degradation have been frequently reported, 29,30 from this initial study no correlation of the degradation products with carbon position was observed. Mapping studies, using a variety of carbons will be probed, as well as in situ mapping investigations to further understand the origin and location of composite electrode degradation.…”
mentioning
confidence: 52%
“…The LiF@Li 2 O‐dominated CEI protects the inner LPSC from decomposition at high current density and voltage, and its thin thickness (6–8 nm) facilitates fast ion‐electron transport through quantum tunneling, resulting in higher capacity at high rates. [ 48 ] Moreover, the crystallized components of the CEI exhibit a wide electrochemical window (e.g., LiF is 0–6.4 V), reducing the decomposition of argyrodite and ensuring intact contact under high voltage. The uniformly dispersed conductive agents and solid electrolytes enable normal operation under thick cathodes, and the excellent compatibility between LPSC‐OF 0.25 and unmodified LCO results in stable operation at high rates, high voltage, and thick cathodes.…”
Section: Resultsmentioning
confidence: 99%
“…Kinetic issues are even enhanced in all-solid-state-batteries (ASSB) using thiophosphate-based solid electrolytes (SE), since the addition of electronic conductive species such as carbon accelerates the degradation of Sbased SE. [4][5][6][7] Equally, the crucial matter of unoptimized ionic and electronic percolation-linked with particle sizes dispersion, mixing process efficiency, and materials surface properties-remains an issue, as reflected by the low first charge capacity obtained in such systems and the high polarization arising from important transport resistances. [8][9][10] In order to investigate these issues and determine kinetic parameters, traditional approaches such as impedance spectroscopy, galvanostatic or potentiostatic intermittent titration techniques, and signature curves are commonly employed.…”
Section: Introductionmentioning
confidence: 99%